Modeling the economic equity of precision oncology - Ioanna Tsatsou; Stavros Fragkopoulos (Journal of Current Health Sciences, 2026)
Precision oncology promises improved outcomes by tailoring treatments to individual tumor profiles. Yet access to genomic testing and targeted therapies remains uneven across socioeconomic groups, raising concerns about equity. This conceptual paper presents an economic framework, utilizing a stylized model and hypothetical illustrations, to demonstrate how unequal access impacts both cost-effectiveness and distributional outcomes in precision oncology. Rather than an empirical study, this work serves as an analytical foundation and review of evidence that show that even when precision oncology is cost-effective overall, disparities in uptake can exacerbate health inequities. Policy interventions that improve equitable access may thus increase both efficiency and fairness in cancer care. Theoretical models, empirical illustration, and policy implications are presented to provide a comprehensive perspective on how health economics can incorporate distributional concerns in the era of precision medicine.